Comparison in antioxidant and antitumor activities of pine polyphenols and its seven biotransformation extracts by fungi - Hui Li; Zhenyu Wang (PeerJ, 2017)
Microbial transformation can strengthen the antioxidant and antitumor activities of polyphenols. Polyphenols contents, antioxidant and antitumor activities of pine polyphenols and its biotransformation extracts by Aspergillus niger, Aspergillus oryzae, Aspergillus carbonarius, Aspergillus candidus, Trichodermas viride, Mucor wutungkiao and Rhizopus sp were studied. Significant differences were noted in antioxidant and antitumor activities. The highest antioxidant activities in Trolox equivalent antioxidant capacity (TEAC), DPPH radical scavenging activity, superoxide anion radical scavenging activity, hydroxyl radical scavenging activity, reducing power assay and antitumor activity against LoVo cells were biotransformation extract of Aspergillus carbonarius (BAC), biotransformation extract of Mucor wutungkiao (BMW), biotransformation extract of Aspergillus carbonarius (BAC), biotransformation extract of Aspergillus niger (BAN), biotransformation extract of Aspergillus oryzae (BAO) and BMW, respectively. Correlation analysis found that antioxidant and antitumor activities were associated with polyphenols contents and types of free radicals and tumors. A. carbonarius can make polyphenol oxidation, hydroxylation and methylation, and form new polyphenols. In conclusion, A. carbonarius, A. niger and M. wutungkiao are valuable microorganisms used for polyphenols biotransformation and enhance the antioxidant and antitumor activities of polyphenols.